The Code: Containing All the Statutes of the State of Iowa, of a General Nature, Passed at the Adjourned Session of the Fourteenth General Assembly Page 76-77, § 456 - (:unkn) unknown (General Publisher, 1873)
Cities and towns shall have the authority to prevent injury and annoyances from transportation and keeping of gunpowder and other combustibles, and licensing of powder magazines.
--
Keywords: GUN POWDER TRANSPORTATION